ER-Golgi network– a future target for anti-cancer therapy - Wlodkowic, Donald (2009)
Tumor cell demise is an important event in the elimination of abnormal malignant cells and provides an important mechanism of natural tumor suppression. Abnormalities incapacitating these finely tuned processes provide a strong advantage for cancer clones to succeed in evading both the physiological control systems and therapeutic intervention. Expanding our knowledge of the molecular “cross-talks” that regulate tumor cell demise is crucial in guiding the successful design of future anti-cancer therapeutics. Although currently available data indicate that elimination of malignant cells often depends on classical apoptotic pathways (mitochondrial and/or death receptor pathways), the evidence is mounting that alternative apoptotic and non-apoptotic pathways may effectively contribute to tumor cell death. The assumption that every organelle is capable of sensing, amplificating and executing cell death is also a relatively novel and unexplored concept. As recently shown, the secretory pathway can be actively involved in sensing stress stimuli and possibly even initiating and propagating cell death signaling. Experimental evidence indicates that ER and Golgi apparatus can activate both pro-survival (recovery) mechanisms as well as cell suicide programs if the stress-signaling threshold is exceeded. It is thus conceivable that the fragile balance of protein trafficking between various subcellular compartments provides an exceptional therapeutic opportunity. Interestingly, a growing number of reports recognize novel therapeutic targets, including proteins in control of endoplasmic reticulum (ER) and Golgi homeostasis. Further studies are, however, needed to elucidate precise signaling pathways emanating from ER-Golgi compartment. Development of more potent and selective small-molecule drugs that activate ER-Golgi mediated cell demise is also needed. As the interest in the role of ER-Golgi network during cancer cell death has been gaining momentum, we attempt here to critically appraise current status of development of investigational anti-cancer agents that target ER and/or Golgi.